2020
DOI: 10.1039/d0ee00838a
|View full text |Cite
|
Sign up to set email alerts
|

Mg3(Bi,Sb)2 single crystals towards high thermoelectric performance

Abstract: Ternary Mg3(Bi,Sb)2 single crystals showing high thermoelectric performance are for the first time grown by the Mg flux method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
107
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 108 publications
(120 citation statements)
references
References 55 publications
2
107
1
2
Order By: Relevance
“…Additionally, a direct revelation of the E g for a semiconductor is possible by carrying out the angle-resolved photoemission spectroscopy (ARPES) on its n -type single crystals [ 26 ]. Pan et al recently reported the ARPES study on n -type Mg 3 Sb 2 single crystal, from which a forbidden gap is clearly observed ( Figure 3(b) ) and an E g > 0.6eV is estimated for Mg 3 Sb 2 [ 48 ]. But since the conduction band was not observed, further study is necessary to accurately determine the real E g .…”
Section: Chemical Bonding and Structurementioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, a direct revelation of the E g for a semiconductor is possible by carrying out the angle-resolved photoemission spectroscopy (ARPES) on its n -type single crystals [ 26 ]. Pan et al recently reported the ARPES study on n -type Mg 3 Sb 2 single crystal, from which a forbidden gap is clearly observed ( Figure 3(b) ) and an E g > 0.6eV is estimated for Mg 3 Sb 2 [ 48 ]. But since the conduction band was not observed, further study is necessary to accurately determine the real E g .…”
Section: Chemical Bonding and Structurementioning
confidence: 99%
“…However, the relatively scarce element tellurium (see Table 1 ) is a potential impediment for the large-scale TE applications of V 2 VI 3 compounds. In recent years, Mg-based semiconductors, e.g., p -type α -MgAgSb [ 44 46 ] and n -type Mg 3 Sb 2- x Bi x [ 33 , 47 , 48 ], have been discovered with good TE performance near RT, comparable to V 2 VI 3 compounds. Magnesium is the 8th most abundant element in the earth's crust [ 49 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the alloying concentration of Mg 3 Bi 2 is crucial for balancing the carrier mobility and the Seebeck coefficient, as well as the bipolar effect. Pan et al [ 33 ] showed the band evolution from Mg 3 Bi 2 to Mg 3 Sb 2 through angle-resolved photoemission spectroscopy (ARPES) combined with density functional theory (DFT) calculations, which also indicated the effectiveness of adjusting the Bi/Sb ratio in improving thermoelectric performance.…”
Section: Electronic Structurementioning
confidence: 99%
“…As discussed above, a Mg deficiency could easily induce a high Mg vacancy ( V Mg 2- ) concentration in the vicinity of the boundary and result in the depletion of free n-type carriers since V Mg 2- serves as an effective electron-killing defect ( Figure 3(d) ). Single-crystal n-type Mg 3 Sb 2 was thus grown and used to investigate the underlying charge-scattering mechanism [ 33 , 57 , 58 ]. As indicated in Figure 3(e) , acoustic phonon scattering dominates the charge transport in the single-crystal sample that lacks grain boundary electrical resistance, resulting in the sample's significantly increased weighted mobility near room temperature.…”
Section: Manipulating the Carrier-scattering Mechanismmentioning
confidence: 99%